2011
DOI: 10.7589/0090-3558-47.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hantavirus Infection in Wild Rodents From Five Provinces in Korea, 2007

Abstract: ABSTRACT:Hemorrhagic fever with renal syndrome (HFRS) is an infectious disease caused by hantaviruses of the family Bunyaviridae. Among them, Hantaan virus (HTNV) is most widely distributed in Korea. The striped field mouse, Apodemus agrarius, is the natural host of HTNV in rural Korea. We trapped 766 small mammals of three species (1 Eothenomys regulus, 13 Crocidura suaveolens, and 752 Apodemus agrarius) in five provinces in Korea from January to December 2007. We tested 542 rodent sera for HTNV antibodies by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
4
17
0
Order By: Relevance
“…There are more Hantavirus-infected rodents in the autumn than there are during other seasons of the year [44, 45]. Seasonally, there are two peaks in the antibody prevalence in striped field mice in April and between September and December.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more Hantavirus-infected rodents in the autumn than there are during other seasons of the year [44, 45]. Seasonally, there are two peaks in the antibody prevalence in striped field mice in April and between September and December.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may contribute to a higher disease incidence in autumn in Korea. This season is characterized by dry weather, increased outdoor activities such as harvesting, and increased rodent entrance into the agricultural fields [20, 27, 30, 45]. Leptospirosis in Korea is mainly transmitted by wild rodents including Apodemus agrarius manchuricus [23].…”
Section: Discussionmentioning
confidence: 99%
“…First, people are more likely to be exposed to the disease because of the increased associated activities, such as harvesting, in rural areas. Second, rodent behavior changes during the autumn climate [ 13 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous report, an almost identical pattern of HFRS incidence was identified in soldiers in endemic areas (7). Higher incidence of HFRS in the autumn, versus other seasons, could be attributed to the high numbers of hantavirus-infected rodents in Korea during this time (10, 11). Seroprevalence of hantaviruses in wild rodents in Korea confidently demonstrated that most wild rodent hantavirus infections occur in the autumn.…”
mentioning
confidence: 99%